Influence of CTAB surfactant on the various properties of CdO nanoparticles and their application in field of dye degradation - Deepak Singhwal; Amita Khatri; Pawan Rana (Journal of Water and Environmental Nanotechnology)
The present work reports the synthesis of Cetyl trimethylammonium Bromide (CTAB) assisted CdO nanoparticles with different concentration of CTAB (0.0M, 0.04M, 0.08M and 0.12M) by co-precipitation and their potential application in photocatalysis. X-Ray Diffraction (XRD) results indicate that crystallite size increases as concentration of CTAB is increased. Field Emission Scanning Electron Microscope (FESEM) exhibit that flat sheet-like morphology is changing into thin needle-like structure with concentration of surfactant. Elemental Dispersive X-ray Spectroscopy (EDS) confirmed existence of constituents and hence marks purity of prepared samples. Broad peak of Raman spectra is consisting of three bands from 200-500 cm-1 while Fourier Transform Infrared (FTIR) spectra certifies vibration of Cd and O bond are present at 530 cm-1. Optical Band gap is found to slightly decrease due to addition of CTAB. Dye degradation results showed that CdO nanoparticles can degrade Methylene Blue (MB) dye and Rose Bengal (RB) Dye degrades upto 83% and 85% respectively within 80 minutes of light irradiation.